Assessing acceptability of pre-exposure prophylaxis (PrEP) among participants in an HIV vaccine preparedness study in southwestern Uganda. - Sarah Nakamanya; Rachel Kawuma; Denis Kibuuka; Sylvia Kusemererwa; Sheena McCormack; Eugene Ruzagira; Janet Seeley; PrEPVacc Study Group (PLoS ONE)
Background Daily oral pre-exposure prophylaxis (PrEP) use is highly effective against HIV infection. However, the uptake of PrEP among individuals at high-risk of HIV acquisition in sub-Saharan Africa varies because of availability and acceptability. We assessed the acceptability of PrEP among participants in a prospective HIV vaccine preparedness study in Masaka, southwestern Uganda. Methods From November 2018 to August 2019, 20 participants (10 female) were purposively selected for in-depth interviews (IDIs) at 3 and 9 months' post-enrolment in the vaccine preparedness study. Four focus group discussions (FGD) (two among men) were conducted with 29 individuals categorized as: younger (18-24 years) men, younger (18-24 years) women, older (≥30 years) men, and older (≥30 years) women. Apart from IDI specific questions on recent life history including work experience, relationship history and places lived, topics for IDIs and FGDs included knowledge of HIV, perceptions of HIV risk (including own risk), knowledge of and use of PrEP. The Theoretical Framework of Acceptability was used to structure a thematic framework approach for data analysis. Results Participants understood that PrEP was an oral pill taken daily by HIV negative individuals to prevent acquisition of HIV. Overall, interest in and acceptability of PrEP was high, more than half expressed positivity towards PrEP but were not ready to initiate taking it citing the burden of daily oral pill taking, related side effects, stigma and distrust of PrEP. Fourteen participants (from IDI and FGD) initiated PrEP, although some (one FGD and two IDI participants) stopped taking it due to side effects or perceived reduced risk. Conclusion We observed a keen interest in PrEP initiation among our study participants. However, a limited understanding of PrEP and associated concerns impeded uptake and sustained use. Hence, interventions are needed to address end-user challenges to increase uptake and support adherence.